Recent advancements in the discovery of protein–protein interaction inhibitors of replication protein A - Patrone, James D. (Royal Society of Chemistry, 2016)

(untitled) (Medchemcomm)
Due to the relatively high rate of DNA damage that can occur during cell cycle progression, the DNA damage response (DDR) pathway is critical for the survival of eukaryotic cells. Replication protein A (RPA) is an essential cell cycle checkpoint protein that mediates the initiation of the DDR by binding to single-stranded DNA (ssDNA) and recruiting response partners via protein–protein interactions (PPIs). This important role of RPA in initiating the DDR and cell survival has led to interest within the scientific community to investigate RPA as a potential cancer drug discovery target. To this end, RPA inhibitors have been explored via a variety of methods. This review summarizes the structure and function of RPA and highlights recent efforts to discover inhibitors of RPA–protein interactions.